Contribuição ao estudo do comportamento dinâmico e aeroelástico de laminados compósitos de rigidez variável - Guimarães, Thiago Augusto Machado (2016)
The developed research work is related to the dynamic and aeroelastic behaviors of variable stiffness composite laminate plates (VSCL). Due to the advances in the manufacturing techniques, this research theme has been gaining international relevance and its importance is justified by the increasing number of research works in this area. In this context, two different types of VSCL are analyzed: the first regards variable fiber spacing laminates, and the second is manufactured using curvilinear paths (tow steering). In order to explore the VSCL characteristics, it was developed an aeroelastic model based on the assumed modes approach (Rayleigh-Ritz), using the hypotheses of “classical lamination theory” (CLT). Moreover, it was used the aerodynamic model based on the quasi-steady strip theory in the subsonic analyses, and the piston theory, for supersonic flows used in the evaluation of panel flutter. It was investigated the influence of different fiber volume distribution on the aeroelastic behavior and on the first three natural frequencies; it has been found that those influences are significant, which justifies the adequate treatment for the micro -structural model of VSCL. Also, to cope with uncertainties during manufacturing of steered composite laminates, it was developed a strategy for identification of those uncertainties and their propagation through the numerical model; also, an optimization procedure was proposed to achieve robust designs. It was noticed that the response of the optimal configuration obtained from deterministic optimization presented a large dispersion when the tow steering angles were perturbed, in contrast with the selected configuration obtained from robust optimization, in which the results were much less sensible to perturbations in the tow steering angles. Also, it was investigated the viability to use LCRV from the dynamic standpoint, aiming at increasing the fundamental frequency, and with application in flutter panel. For both applications, the fiber placement trajectory was optimized based on Lagrange polynomials. Reasonable gains were found with respect to constant stiffness composite laminates (CSCL). Additionally, it was verified that the obtained experimental results for VSCL and CSCL corroborate the counterparts obtained from numerical simulations regarding natural frequencies and mode shapes.